The Effectiveness of the Use of Pedagogical Technologies in Improving Literacy of Primary Students - G'anijonova Sarvinoz Bahodirovna (Scientific Trends, 2025)
This study studies the effectiveness of the use of pedagogical technologies in improving literacy of Primary School students. The article analyzes the role of digital and traditional pedagogical technologies in the development of literacy skills in the modern educational system. Literature analysis shows that pedagogical technologies have a positive effect on the development of reading, writing and speech by students. The results of the study demonstrated the effectiveness of interactive methods, digital tools and multimedia technologies in increasing the literacy rate of primary students.
Keywords: Pedagogical technologies, literacy, primary education, digital technologies, reading skills, interactive methods